Implementasi Kurikulum Merdeka Tema “Aku Sayang Bumi” Pada Anak Usia Dini di Ra Al Jihad Malang - Rochmah, Ainur; Mupi Anisah; Rahmi; Laila Nur Fitriah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research was conducted to determine the role of teachers/child assistants in implementing and the influence of implementing a merdeka curriculum system with the theme "I Love the Earth" on children's character from an early age at RA AL Jihad Malang. The type of research is qualitative with a case study approach method. Researchers used data collection techniques using interviews, documentation, FGD, and observation. The data obtained was analyzed using the Miles and Huberman technique which consists of four stages, ensuring data collection, data reduction, data presentation, and conclusions. The credibility test that the researcher carried out was through technical triangulation and source triangulation. It was found that the implementation of merdeka curriculum with the theme I love the earth has been implemented in full at the RA Al Jihad school since last year. The implementation of the curriculum is designed by teachers together concerning the academic calendar. The method that the teacher chooses in learning is the method of habituation and coaching as a way of instilling these character values. for example, through project activities such as processing compost, and planting kale and habits in daily life such as praying in the morning. The influence that can be felt on children is the realization of character formation such as religious character, honesty, tolerance, discipline, hard work, creativity, independence, curiosity, communicativeness, respect for achievement, and social care.